2010
DOI: 10.1108/03090591011061202
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between diversity training, organizational commitment, and career satisfaction

Abstract: Purpose-The purpose of this paper is to investigate the association between employees' perceptions of diversity training (DT) existence and effectiveness with organizational commitment (OC), and career satisfaction (CS). Design/methodology/approach-The analyses in this paper utilize survey data collected between 2006 and 2007 from over 11,000 managers, professionals, and executives working in nine large organizations in corporate Canada. The survey included questions about employees' perceptions of their work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 64 publications
(118 reference statements)
2
35
1
Order By: Relevance
“…These results didn't coincide with the results of (El-Masarwah 2011) Yap et al, (2010), Reynolds et al (Ashikali & Groeneveld 2014).…”
Section: Discussion and Recommendationscontrasting
confidence: 56%
“…These results didn't coincide with the results of (El-Masarwah 2011) Yap et al, (2010), Reynolds et al (Ashikali & Groeneveld 2014).…”
Section: Discussion and Recommendationscontrasting
confidence: 56%
“…Employees' career satisfaction occurs when the organization provides them with the expected programs (Chiaburu, Diaz & De Vos, 2013). Yap, Holmes, Hannan and Cukier (2010) contend that employees were more satisfied with their careers when they perceived effective diversity training. Furthermore, OCM practices can improve employees' organizational commitment levels (Bambacas, 2010).…”
Section: Organizational Career Managementmentioning
confidence: 99%
“…A research from Taormina (1999) also revealed that training was a crucial predictor of job satisfaction. Another previous study from Yap et al (2010) also found that the employee that recognized diversity training to be effective has higher job satisfaction. Therefore, proper training should be given to academic staffs from time-to-time, to upgrade and update their skills so as to enhance their capabilities and abilities.…”
Section: Hypothesismentioning
confidence: 91%
“…There was a study of Yap and Holmes (2010) which investigated the association between employees' perceptions of diversity training (DT) existence and effectiveness with organizational commitment (OC), and career satisfaction (CS). The paper also examined the linkages between diversity training, organizational commitment, and career satisfaction based on survey responses from managers, professionals, and executives.…”
Section: Training and Development (Tandd)mentioning
confidence: 99%